Physico-hydric behavior of a Red Yellow Cambic Podzolic soil terrace phase under different management systems - Carvalho, Eduardo Jorge Maklouf; Figueiredo, Matozinho de Souza; Costa, Liovando Marciano da (Pesquisa Agropecuaria Brasileira, 1999)
The study was carried out in the county of Viçosa, MG, Brazil, in the campus of Universidade Federal de Viçosa (UFV). The objective was to study the physico-hydric behavior of a Red Yellow Cambic Podzolic soil terrace phase under different management systems. The experimental design was a completely randomized block design, with five treatments and four replications. Treatments were: 1- moldboard plow; 2- disk plow; 3- heavy disk harrow; 4- no tillage; 5- control (fallow). Organic matter, texture, bulk density, particle density, total porosity, macro-porosity and micro-porosity, agregates and soil moisture tension curves were measured. Results indicate that: soil organic matter is slightly greater in no-tillage and control plots, and reduces in heavy disk plots in the surface 15 cm of the profile; cultivation with heavy machinery increases soil bulk density only slightly in the surface 15 cm of the soil profile; soil tillage increases macroporosity; no-till and control plots show greater aggregate stability; no-tillage plots have greater water holding capacity.